TEACHER'S TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN NEW NORMAL ERA - Imadul Bilad; Achmad Anang Darmawan; Lina Aris Ficayuma (Journal of English Language Teaching and Islamic Integration, 2023)
Recognizing that each teacher has unique strengths, preferences, and learning styles, they tailored their instructional approach accordingly. By  aligning  their  teaching  methods  with  their  own  characteristics,  they  were  able  to  optimize TPACK  development  and  create  meaningful  and  engaging  learning  experiences  for  their students.